Characterization of apolipoprotein E-deficient rats as novel model for atherosclerosis imaging. (20th July 2021) - Sijbesma, JWA; Van Waarde, A; Kristensen, S; Kion, I; Tietge, UJF; Hillebrands, JL; Buikema, H; Nakladal, D; Liu, F; Boersma, HH; Dierckx, RAJO; Slart, RHJA
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The apolipoprotein E-deficient (apoE-/-) mouse is a well-established atherosclerotic model with impaired lipoprotein clearance and development of vessel plaques. However, the small size of the mouse limits its use as an animal model in longitudinal positron emission tomography (PET) imaging studies of atherosclerosis. Recently, apoE-/- rats have become available. This study addresses the suitability of the apoE-/- rat as model for atherosclerotic PET imaging. Methods: Ten male apoE-/- rats and ten male control rats (apoE+/+) (age 10+/-1 weeks), each fed with a Western diet, were injected at baseline week 4, 12, 26 and 51, with 60 MBq of [18F]2-fluoro-2-deoxy-D-glucose. Plasma cholesterol, body weight and fat were measured. 3h after injection, a computed tomography (CT) and a 20-min PET scan were made. After the final scan, aortic tissue was collected for histological staining. Results: Cholesterol levels started to increase after 4 weeks in the apoE-/- rats, whereas in the apoE+/+ rats levels stayed stable. Body weight and body fat increased more rapidly in the apoE-/- rats but were similar in both strains at the end of the study. SUVmean and max in the aortic arch and abdominal aorta were significantly higher (p < 0.001) in apoE-/- versus apoE+/+ rats at weeks 12, 26 and 51. Oil red O staining showed lesions in 20.0 % of the surface of the aortic arch in the apoE-/- rats. Hardly no fatty streaks were detected in the apoE+/+ rats (2.29%). More histology data is being analyzed. Conclusion: Plasma cholesterol levels were elevated in apoE-/- rats. PET imaging demonstrated differences in [18F]-FDG uptake in the aortic arch and abdominal aorta after 12, 26 and 51 weeks. Combined, these data demonstrate that apoE-/- rats represent a useful preclinical model for the non-invasive assessment of atherosclerosis in longitudinal studies.